2009
DOI: 10.5194/acp-9-7901-2009
|View full text |Cite
|
Sign up to set email alerts
|

A new transport mechanism of biomass burning from Indochina as identified by modeling studies

Abstract: Abstract. Biomass burning in the Indochina Peninsula (Indochina) is one of the important ozone sources in the low troposphere over East Asia in springtime. Moderate Resolution Imaging Spectroradiometer (MODIS) data show that 20 000 or more active fire detections occurred annually in spring only from 2000 to 2007. In our tracer modeling study, we identify a new mechanism transporting the tracer over Indochina that is significantly different from the vertical transport mechanism over the equatorial areas such as… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
66
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(76 citation statements)
references
References 43 publications
4
66
0
Order By: Relevance
“…Surface and ozonesonde measurements in southern China in the spring showed significant enhancements in CO, black carbon aerosol (BC), PM 2.5 , PM 10 , and ozone when the local air was impacted by air masses back-traceable to PSEA (Liu et al, 1999;Chan et al, 2000;Deng et al, 2008;Lin et al, 2009Yen et al, 2012). Using a regional model, Fu et al (2012) found that the long-range transport of PSEA biomass-burning emissions during spring 2006 contributed significantly to the monthly mean surface concentrations of CO (20-50 %), ozone (10-30 %), and PM 2.5 (10-70 %) in southern China, as well as leading to 2-5 ppbv ozone enhancement in the lower troposphere over the western Pacific.…”
Section: Y Jian and T-m Fu: Injection Heights Of Springtime Biomasmentioning
confidence: 99%
“…Surface and ozonesonde measurements in southern China in the spring showed significant enhancements in CO, black carbon aerosol (BC), PM 2.5 , PM 10 , and ozone when the local air was impacted by air masses back-traceable to PSEA (Liu et al, 1999;Chan et al, 2000;Deng et al, 2008;Lin et al, 2009Yen et al, 2012). Using a regional model, Fu et al (2012) found that the long-range transport of PSEA biomass-burning emissions during spring 2006 contributed significantly to the monthly mean surface concentrations of CO (20-50 %), ozone (10-30 %), and PM 2.5 (10-70 %) in southern China, as well as leading to 2-5 ppbv ozone enhancement in the lower troposphere over the western Pacific.…”
Section: Y Jian and T-m Fu: Injection Heights Of Springtime Biomasmentioning
confidence: 99%
“…Particular attention was given to PM 10 emissions since PM 10 concentrations usually exceed those of other gases emitted during forest fires and the WHO (World Health Organization) guidelines (Radojević and Hassan, 1999). Most studies on BBH have been restricted to immediate dispersion and haze trajectories to neighboring countries (Lin et al, 2009) when measurements have showed that deep convection in SEA can lift biomass-burning emissions up in the troposphere (Folkins et al, 1997). It is therefore important to get a better understanding of the uplifting mechanisms, and this is a gap that this study aims to fill.…”
Section: Introductionmentioning
confidence: 99%
“…A strong convection mechanism responsible for the uplifting of biomass-burning emissions over Indonesia, New Guinea and Malaysia has also previously been at the center of discussions (Folkins et al, 1997). Lin et al (2009) have identified leeside troughs over Indochina as major contributors to the uplifting of the tracer in a tracer modelling study while Cheng et al (2013) have identified that biomassburning emissions were lifted due to thermal forcinginduced upward motion and high terrain in the northern part of SEA. While the uplifting mechanisms have been studied in Indochina, there is a need to identify the convective mechanisms responsible for the uplifting of biomass-burning emissions in Southern SEA, as literature in this region on the mechanisms remain scarce.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations